IL-1beta expressing neutrophil extracellular traps in Legionella pneumophila infection - Myrto Koutantou; Theocharis Konstantinidis; Dimosthenis Chochlakis; Evangelia Xingi; Anna Psaroulaki; Georgios Tsiotis; Konstantinos Kambas; Emmanouil Angelakis (Frontiers in Immunology)
IntroductionLegionella pneumophila is the causative agent of Legionnaires’ Disease (LD), an atypical pneumonia with potentially fatal outcome. Neutrophils, the first line of defense, infiltrate the lungs during L. pneumophila infection, although the precise immune mechanisms involved remain unclear.MethodsThis study aims to examine in vitro the interaction of neutrophils with L. pneumophila. Neutrophils from healthy individuals were infected with opsonized and non-opsonized bacteria. Phagocytosis was assessed by immunolabeling, and reactive oxygen species (ROS) generation by flow cytometry. The ability of neutrophils to form Neutrophil Extracellular Traps (NETs) in response to L. pneumophila and the impact of these NETs on bacterial proliferation were examined. Immunolabeling and Western blotting were used for specific NET-associated epitope detection.ResultsIt was demonstrated that neutrophils phagocytose opsonized L. pneumophila, while non-opsonized bacteria were not phagocytosed. Opsonized bacteria triggered ROS production, unlike non-opsonized bacteria. Neutrophils released NETs upon L. pneumophila interaction in a ROS-independent manner, but these NETs failed to inhibit bacterial proliferation. Notably, IL-1b was detected on NETs.DiscussionThis study provides evidence that neutrophils react to L. pneumophila through phagocytosis, the production of ROS, and NET release. IL-1b on NETs could play a role in complicated LD cases. These findings contribute to the understanding of neutrophil-mediated immune responses in LD.